Locally led adaptation and climate-smart agriculture: A review of two conceptual framings of responses to climate change in LMICs - Habermann, Birgit (CAB International, 2025)
Climate change has an enormous impact on farming communities in low- and middle-income countries (LMICs). Two prominent responses to support governments and communities in responding to this are locally-led adaptation (LLA) and climate-smart agriculture (CSA). LLA and CSA rarely overlap, partly because LLA is more process-oriented, and CSA is more technology oriented; additionally, they are situated in different actor-networks. Hence, there are few literatures addressing both at the same time, even though both operate in the field of climate change. With this review, I aim to elicit potential synergies between the two topically related concepts to understand what motivations become apparent when scientists use either LLA or CSA as conceptual framing in their publications; how LLA or CSA can be adapted conceptually to be more needs- and place-oriented as opposed to being driven by international donor communities and political agendas; and finally, if there is any benefit in seeking overlap between LLA and CSA. For this purpose, I conducted a systematic literature review combined with qualitative data analysis with NVivo. Following elimination through screening, most of the remaining articles were focused only on LLA; therefore, most of the review addresses LLA and then eliciting overlap and potential synergy in the final part of this article. The review of 29 studies showed that the most frequently addressed themes in LLA literature are power and agency, governance, and motivations for change, whether driven by donors, place, or local needs. Despite strong rhetorical support for LLA, implementation often falls short, with many interventions still reflecting top-down, externally driven processes that contradict LLA principles. While some case studies demonstrate that locally grounded governance systems can enable more effective adaptation, questions remain about the scalability, legitimacy, and conceptual clarity of LLA, particularly in relation to frameworks like CSA. To ensure LLA contributes meaningfully to adaptation and complements CSA, greater attention must be given to governance, locally defined priorities, and the socio-political realities of decision making. Moving forward, bridging the divide between global frameworks and local agency requires critical reflection on language, power, and the role of external actors in shaping adaptation pathways.